2015
DOI: 10.3109/08958378.2015.1030480
|View full text |Cite
|
Sign up to set email alerts
|

Association between copper levels and myocardial infarction: a meta-analysis

Abstract: This meta-analysis indicates a significant association between high serum Cu levels and MI. However, the subgroup analysis found that there was significant effect modification of Cu levels by ethnicity. Thus, we suggest that a trans-regional multicenter study is needed to obtain better understanding of causal relationships between Cu and MI in different human races.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
(51 reference statements)
2
13
0
Order By: Relevance
“…As a strong prooxidant, Cu may play a role in the development of atherosclerosis, which underlies cardiovascular diseases [23]. Similarly to the present study, the meta-analysis by Chan et al [24] indicated that a higher concentration of Cu was found in the blood serum of post-MI individuals as compared to those in the healthy group. Altekin et al [25] noticed a positive correlation between the level of Cu in the serum and the markers of myocardial damage, including cardiac troponin T and troponin I, and mass concentration of creatine kinase isoenzyme MB.…”
Section: Discussionsupporting
confidence: 83%
“…As a strong prooxidant, Cu may play a role in the development of atherosclerosis, which underlies cardiovascular diseases [23]. Similarly to the present study, the meta-analysis by Chan et al [24] indicated that a higher concentration of Cu was found in the blood serum of post-MI individuals as compared to those in the healthy group. Altekin et al [25] noticed a positive correlation between the level of Cu in the serum and the markers of myocardial damage, including cardiac troponin T and troponin I, and mass concentration of creatine kinase isoenzyme MB.…”
Section: Discussionsupporting
confidence: 83%
“…Acute coronary syndrome (ACS) is a severe CVD subtype with high mortality, including acute myocardial infarction (AMI) and unstable angina (UA). A previous meta-analysis of 19 case-control studies showed a significant positive association between high serum Cu level and myocardial infarction [5]. In a prospective cohort study of 1666 participants in eastern Finland, researchers observed that serum copper concentration in the two highest tertiles associated with 3.5-fold and 4.0-fold risk of AMI [6].…”
Section: Introductionmentioning
confidence: 95%
“…Conversely, because of the role of copper in catalyzing oxidation-reduction reactions, which play an important role in the pathogenesis of CHD, copper may also play a role in atherogenesis. High serum copper levels have been linked to an increased risk of atherosclerotic CVDs in a number of observational case-control [11] and cohort studies [12,13]. Previously reported associations between serum copper and CVD outcomes have mostly been inconsistent.…”
Section: Introductionmentioning
confidence: 99%